Pengaruh Kualitas Fitur, Influencer Marketing dan Harga Terhadap Keputusan Berlangganan Canva Premium Pad Generasi Z dikota Sumbawa - Rati Putriani; Agus Santoso (Jurnal Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the effects of feature quality, Influencer Marketing, and price on subscription decisions for Canva Premium among Generation Z in Sumbawa City. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z respondents who had used Canva Premium, selected using purposive sampling. The data were analyzed using multiple linear regression accompanied by partial t-tests. The results indicate that feature quality and price have a positive and significant effect on Canva Premium subscription decisions. In contrast, Influencer Marketing does not have a significant effect on subscription decisions. These findings suggest that Generation Z places greater emphasis on functional and rational considerations, such as ease of use, feature completeness, and price affordability, rather than promotional influence from influencers. This study is expected to contribute theoretically to digital consumer behavior research and provide practical insights for companies in developing more effective digital service marketing strategies tailored to the characteristics of Generation Z.